THE INFLUENCE OF ORGANIZATIONAL JUSTICE AND ORGANIZATIONAL CULTURE ON ORGANIZATIONAL COMMITMENT WITH JOB SATISFACTION AS AN INTERVENING VARIABLE IN BPJS EMPLOYMENT OF ACEH PROVINCE - Furat Siswara, Aqil; B, Mesra (Penerbit Lafadz Jaya, 2023)
This research aims to see the direct and indirect influence between the variables of organizational justice and organizational culture as independent variables and job satisfaction as an intervening variable and organizational commitment as the dependent variable. This type of research uses quantitative, this research was conducted at BPJS Employment Aceh Province. The population and sample of this research were 50 employees. The data source used is a primary data source and data collection is carried out by distributing questionnaires. The research model used is path analysis with smart PLS version 3.3.3. The results of this research are that organizational culture has a positive and significant effect on job satisfaction. Organizational culture has a positive but not significant effect on organizational commitment. Organizational justice has a positive and significant effect on job satisfaction. Organizational justice has a positive and significant effect on organizational commitment. Job satisfaction has a positive and significant effect on organizational commitment. Organizational culture has a positive and significant effect on organizational commitment through job satisfaction. Organizational justice has a positive and significant effect on organizational commitment through job satisfaction.